Pengaruh Penerapan Terapi Suportif Terhadap Kejadian Post Partum Blues Di Desa Banjar Negoro Kec. Wonosobo Kab. Tanggamus - Dainty Maternity; Rilyani Rilyani; Maissy Hardianti (Universitas Malahayati Lampung, 2021)
Introduction: According to the World Health Organization (WHO, 2017), in terms of gender, the female group recorded the highest incidence of mood disorders which was 5.1%; compared to males 3.6% (WHO, 2017). in terms of age, the incidence of mood disorders is high in the environment of late adulthood between 55 years to 74 years (7.5% women: 5.5% men) (WHO, 2017). Mental mood disorders occur in Southeast Asian countries 27% compared to other overseas like Africa (9%), Eastern Mediterranean (16%), Europe (12%), America (15%), and the West Pacific (21%) (WHO, 2017)Objective: To find out the benefits of applying supportive therapy in postpartum with the occurrence of baby blues in Banjar Negoro Village, Kec. Wonosobo Kab. Lampung Province Tanggamus in 2019.Method: This type of research is quantitative. The research design of the Quasi-Experimental method is one group pretest-posttest one group pretest-posttest approach. The population and sample were 20 people. Data analysis uses univariate and bivariate using t-tests.Results: Postpartum blues in postpartum mothers before the application of supportive therapy in postpartum mothers obtained an average EPDS score of 25.47 with the lowest EPD score of 18 and the highest EPD value of 30, and after the application of supportive therapy in postpartum mothers obtained an average EPDS score of 14.29 with the lowest EPD score of 9, and the highest EPD score of 20, with a mean difference test of 12.100. The results of statistical tests using dependent tests obtained p-values of 0,000 (α 0.05).Conclusion: This means that there is an influence of the application of supportive therapy to the incidence of postpartum blues in the village of Banjar Negoro Kec. Wonosobo Tanggamus Lampung Province in 2019. The results of this study can be used as an alternative treatment for clinics or places of care if you find patients with postpartum blues can use effective supportive therapy given to reduce the anxiety suffered.Keywords: Supportive Therapy, Post Partum, Genesis Baby Blues Pendahuluan: Menurut World Health Organization (WHO, 2017)[U2] , dari segi gender golongan wanita mencatatkan kadar kejadian gangguan mental kemurungan paling tinggi yaitu 5.1%; berbanding lelaki 3.6% (WHO, 2017). dilihat segi umur, kejadian gangguan mental kemurungan adalah tinggi dalam lingkungan umur dewasa akhir di antara 55 tahun hingga 74 tahun (7.5 % wanita : 5.5% lelaki) (WHO, 2017). Kejadian gangguan mental kemurungan terjadi di negara Asia Tenggara 27% berbanding lain-lain rantau seperti Afrika (9%), Timur Mediterranean (16%), Eropa (12%), Amerika (15%) dan Barat Pasifik (21%) (WHO, 2017)[U3] . Tujuan: Diketahui manfaat penerapan terapi suportif pada post partum dengan kejadian baby blues di Desa Banjar Negoro Kec. Wonosobo Kab. Tanggamus Provinsi Lampung Tahun 2019.Metode: Jenis penelitian ini adalah Kuantitatif. Desain penelitian metode Quasi Eksperimental pendekatan one group pretes-postes one group pretes-postes. Populasi dan sampel sebanyak 20 orang. Analisa data mengguanakan univariat dan bivariate dengan t-tes.Hasil : Post partum blues pada ibu post partum sebelum penerapan terapi suportif pada ibu post partum didapat nilai rata-rata skor EPDS sebesar 25,47 dengan skor nilai EPD terendah 18 dan nilai nilai EPD tertinggi 30, dan sesudah penerapan terapi suportif pada ibu post partum didapat nilai rata-rata skor EPDS sebesar 14,29 dengan skor nilai EPD terendah 9, dan skor nilai EPD tertinggi 20, dengan nilai uji beda mean 12,100. Hasil uji statistik menggunakan tes-dependen didapat nilai p-value 0.000 (α0.05).Kesimpulan : Artinya terdapat pengaruh penerapan terapi suportif terhadap kejadian post partum blues di Desa Banjar Negoro Kec. Wonosobo Tanggamus Provinsi Lampung Tahun 2019. Hasil penelitian ini dapat digunakan sebagai alternatif pengobatan bagi klinik atau tempat perawatan, jika menemukan pasien dengan post partum blues dapat menggunakan terapi suportif yang efektif diberikan untuk mengurangi cemas yang diderita.